Financing Investment in Times of High Public Debt: 2023 European Public Investment Outlook - FLORIANA MARGHERITA CERNIGLIA; Francesco Saraceno; Andrew Watt (Open Book Publishers, 2023)
The fourth book in the 'European Public Investment Outlook' series focuses on the urgent issue of how to finance needed investment in critical tangible and intangible infrastructure given high levels of public debt, a thorny problem facing many governments across Europe. Drawing on expertise from academics, researchers at public policy institutes and international governance bodies, the contributors analyse the current situation and prospects and propose feasible solutions. Financing Investment in Times of High Public Debt offers a powerful combination of high-level analysis of cross-continental policies and trends, with close examination of specific contexts in France, Italy, Germany and Spain. The chapters in Part II explore challenges including how to finance climate investments, the extent to which national promotional banks can offer solutions, EU budget reform and recent trends in tax progressivity. This book is essential reading for economists, policymakers, and anyone interested in implementing and financing public policy in Europe and wanting to better understand the intricacies of EU governance and institutions.
Keywords: 330; Financing; European economics; Investment; Public debt; Infrastructure; Governance